Ayurvedic Management of Kitibha Kustha (Plaque Psoriasis) with Ojo-Vyapat Chikitsa: A Case Report - Dr. Khushal Choudhary; Dr. Bhavin V. Dhanavade; Dr. Suwarna A. Meshram; Dr. Dnyaneshwar M. Gadade (The Bioscan, 2026)
This clinical case study highlights the successful Ayurvedic management of chronic plaque psoriasis, identified as Kitibha Kushta in classical texts. A 48-year-old obese female presented with erythematous, scaly plaques over the trunk and upper limbs, persisting for six years with inadequate response to conventional treatments, including corticosteroids and methotrexate. She sought Ayurvedic intervention after facing recurrence and diminished relief from allopathic therapies. Based on Ayurvedic assessment, the patient was diagnosed with Kitibha Kushta involving Vata-Kapha Dushti, with systemic involvement of Twak, Rakta, Mamsa, and Lasika Dhatus. The treatment protocol involved “Ojovyapat Chikitsa” followed by “Shamana Snehapana using Mahatiktaka Ghrita”, and internal medications such as Punarnavadi Kashayam, Shaddharana DS, Amruttashadanga Kashaya, and Guduchi Paneeya. Dietary and lifestyle modifications were strictly advised. Remarkable clinical improvement was seen with an 81.4% reduction in PASI (from 10.5 to 1.95) and a 76.2% improvement in DLQI (from 21 to 5). ANA, CRP, ESR, and IgE levels normalized. No relapse or adverse effects occurred over four months. Ayurvedic management in chronic autoimmune skin disorders, even without Panchakarma, offered a non-invasive, immune-corrective approach resulting in sustained remission and high patient satisfaction. It offers a promising alternative in managing psoriasis where conventional treatments fail or are contraindicated.